2021
DOI: 10.1021/jacs.1c05586
|View full text |Cite
|
Sign up to set email alerts
|

Ladder Phenylenes Synthesized on Au(111) Surface via Selective [2+2] Cycloaddition

Abstract: Ladder phenylenes (LPs) composed of alternating fused benzene and cyclobutadiene rings have been synthesized in solution with a maximum length no longer than five units. Longer polymeric LPs have not been obtained so far because of their poor stability and insolubility. Here, we report the synthesis of linear LP chains on the Au(111) surface via dehalogenative [2+2] cycloaddition, in which the steric hindrance of the methyl groups in the 1,2,4,5-tetrabromo-3,6-dimethylbenzene precursor improves the chemoselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 71 publications
3
54
0
Order By: Relevance
“…In the past decade, on‐surface reactions have provided a unique pathway for the atomically precise synthesis of novel nanostructures, [11–25] including graphene nanoribbons, [14, 15] cyclo[18]carbon, [16] and biphenylene sheets [17] . Recently, several cycloaddition reactions have been achieved on surfaces, [26–37] such as azide–alkyne cycloaddition, [26, 27] Diels–Alder reaction, [28–30] the [2+2+2] cyclotrimerization of alkynes, [31] the dehalogenative [2+2] [32] and [2+2+2] cycloaddition of ortho ‐dihalogenated arenes, [33] and the [3+2] cycloaddition of azomethine ylide and cyano, [34] which provide various carbocycles and heterocycles. More recently, Li et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decade, on‐surface reactions have provided a unique pathway for the atomically precise synthesis of novel nanostructures, [11–25] including graphene nanoribbons, [14, 15] cyclo[18]carbon, [16] and biphenylene sheets [17] . Recently, several cycloaddition reactions have been achieved on surfaces, [26–37] such as azide–alkyne cycloaddition, [26, 27] Diels–Alder reaction, [28–30] the [2+2+2] cyclotrimerization of alkynes, [31] the dehalogenative [2+2] [32] and [2+2+2] cycloaddition of ortho ‐dihalogenated arenes, [33] and the [3+2] cycloaddition of azomethine ylide and cyano, [34] which provide various carbocycles and heterocycles. More recently, Li et al.…”
Section: Methodsmentioning
confidence: 99%
“…In the past decade, on-surface reactions have provided a unique pathway for the atomically precise synthesis of novel nanostructures, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] including graphene nanoribbons, [14,15] cyclo [18]carbon, [16] and biphenylene sheets. [17] Recently, several cycloaddition reactions have been achieved on surfaces, [26][27][28][29][30][31][32][33][34][35][36][37] such as azide-alkyne cycloaddition, [26,27] Diels-Alder reaction, [28][29][30] the [2+2+2] cyclotrimerization of alkynes, [31] the dehalogenative [2+2] [32] and [2+2+2] cycloaddition of ortho-dihalogenated arenes, [33] and the [3+2] cycloaddition of azomethine ylide and cyano, [34] which provide various carbocycles and heterocycles. More recently, Li et al reported the one-step [1+1+1+1] cycloaddition of phenylacetylenes to achieve the synthesis of tetraphenyl- [4]radialenes on Cu(100); [38] this is the only example of the synthesis of radialenes on a surface to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12). 147 The electronic properties of LP were examined by scanning tunnelling spectroscopy (STS) measurements after transferring the LP chains from the metal surface to NaCl islands via tip manipulation. LP was found to be positively charged, with singly occupied (SOMO) and associated unoccupied (SUMO) molecular orbitals identified by d I /d V maps and confirmed by density functional theory (DFT) calculations.…”
Section: Synthesis Of Clps From Aromatic Ring Monomersmentioning
confidence: 99%
“…Nanoribbons with four-membered rings, however, have so far remained elusive due to challenges in their chemical synthesis (38). Although [2 + 2] cycloaddition has been shown to generate four-membered rings via on-surface synthesis, it has so far only been used to couple smaller acenes and triphenylenes (31,(39)(40)(41)(42). The CBD units in these systems exhibit relatively little antiaromaticity due to their fusion pattern (i.e., because the CBD bonds have more single bond character in the dominant resonance structures that maximize the number of Clar sextets), resulting in a large bandgap (31,36,43).…”
Section: Introductionmentioning
confidence: 99%